A cross sectional study to assess the vaccination practices regarding hepatitis B among health care personnel of a tertiary care hospital in Kashmir - Gulzar, Basina; Fazili, Anjum; Shah, Rohul Jabeen; Ain, Syed Najmul (International Journal Of Community Medicine And Public Health, 2023)
Background: Vaccination is one of the most successful public health interventions that has saved millions of lives so far. Due to the occupational exposure, health care workers have an increased risk of contracting hepatitis B. Objectives were to assess the vaccination practices regarding hepatitis B among healthcare personnel (HCP) and to study the factors associated with the vaccination practices regarding hepatitis B of these HCP. Methods: This cross sectional hospital based study was conducted for a period of 1 year at Sher-I-Kashmir Institute of Medical Sciences (SKIMS) among 450 HCP including doctors, nursing staff, laboratory staff and others and the required sample was drawn from each category on the basis of probability proportionate to size technique. Information was collected from participants by using predesigned, pretested structured and validated questionnaire. Results: It was found that only 34.9% were vaccinated against hepatitis B. The coverage was highest among doctors 55.5% followed by technicians 25.6%, nurses 23.6%. The main reasons for not receiving this vaccine were: taking all necessary precautions (49.1%), hospital does not provide the vaccine (20.8%), not aware about hepatitis B vaccine (20.5 %). Conclusions: The study revealed that the hepatitis B vaccination coverage of these healthcare personnel was quite low in spite of the importance of the vaccine for healthcare personnel who are always at risk of getting exposed to the virus during their duties.